2013
DOI: 10.1164/rccm.201207-1279oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prone Positioning on Lung Protection in Patients with Acute Respiratory Distress Syndrome

Abstract: Prone positioning enhances lung recruitment and decreases alveolar instability and hyperinflation observed at high PEEP in patients with ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
183
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(203 citation statements)
references
References 45 publications
9
183
0
11
Order By: Relevance
“…The improvement of the ventilation/perfusion ratio is determined by positioning the ventilated alveoli in the dependent regions, where perfusion gravitationally predominates, and by decreasing the overdistension of ventral areas, with a reduction of alveolar wall injury. Indeed, prone positioning was demonstrated to enhance lung recruitment and to decrease alveolar instability at the same time [25,26]. A significant improvement of PaO 2 /FIO 2 has been shown by ventilating patients in the prone position [27].…”
Section: Computed Tomographymentioning
confidence: 98%
“…The improvement of the ventilation/perfusion ratio is determined by positioning the ventilated alveoli in the dependent regions, where perfusion gravitationally predominates, and by decreasing the overdistension of ventral areas, with a reduction of alveolar wall injury. Indeed, prone positioning was demonstrated to enhance lung recruitment and to decrease alveolar instability at the same time [25,26]. A significant improvement of PaO 2 /FIO 2 has been shown by ventilating patients in the prone position [27].…”
Section: Computed Tomographymentioning
confidence: 98%
“…Prone positioning Prone positioning Prone positioning Prone positioning Prone positioning The prone position is a relatively simple and safe method for improved oxygenation, which can be regarded as a recruitment maneuver itself, improving gas exchange, promoting alveolar recruitment, without providing areas of hyperinflation 2,9 . When patients are placed in the prone position, the chest wall compliance decreases, and the P TP is redistributed from dorsal to ventral and, as a consequence, there is a recruitment of pulmonary dorsal regions, which directly reflects the improvement in patient's oxygenation [10][11][12] .…”
Section: Methods Methods Methods Methodsmentioning
confidence: 99%
“…Direct proof of VILI is nearly impossible to obtain in "real" ARDS patients, but a recent PET study [16] showed that the nonhomogeneous lung regions at the interface between collapsed and inflated lung tissue, where putatively intra-tidal collapse and decollapse occur, are always inflamed. Despite the relevance of the issue of opening and closing, just two studies measured intra-tidal collapse and decollapse at two different PEEP levels keeping the tidal volume constant and both were unable to demonstrate a significant intra-tidal collapse and decollapse reduction [11,18]. We measured intra-tidal collapse and decollapse in 34 ARDS patients (18 severe ARDS) keeping the tidal volume constant at two PEEP levels, 5 and 15, which are close to the PEEP levels applied in all clinical trials.…”
Section: Is Opening and Closing Real And What Is The "Real" Effect Ofmentioning
confidence: 99%